2022
DOI: 10.2174/1570159x20666220302101115
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Investigation of Glutamate Levels and Percentage Gray Matter in the Medial Prefrontal Cortex in Females at Risk for Postpartum Depression

Abstract: The substantial female hormone fluctuations associated with pregnancy and postpartum have been linked to a greater risk of developing depressive symptoms, particularly in high-risk women (HRW), i.e. those with histories of mood sensitivity to female hormone fluctuations. We have shown that glutamate (Glu) levels in the medial prefrontal cortex (MPFC) decrease during perimenopause, a period of increased risk of developing a major depressive episode. Our team has also demonstrated that percentage gray matter (%G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…A limitation of this study was that sample sizes were relatively small for both PM ( n = 18) and RD ( n = 20) groups. However, we were able to show decreased GABA+ and/or Glu ratios in similar or smaller samples that investigated the impact of reproductive status on these metabolites ( 3 , 18 , 33 ). We do not believe that our negative results are explained by a small sample size and therefore by a type II error.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A limitation of this study was that sample sizes were relatively small for both PM ( n = 18) and RD ( n = 20) groups. However, we were able to show decreased GABA+ and/or Glu ratios in similar or smaller samples that investigated the impact of reproductive status on these metabolites ( 3 , 18 , 33 ). We do not believe that our negative results are explained by a small sample size and therefore by a type II error.…”
Section: Discussionmentioning
confidence: 67%
“…However, Cr+PCr have been used extensively as a reference molecule in previous MRS MD research ( 42 ). In addition, our group recently demonstrated that Cr+PCr was unaffected by the large female hormone changes experienced during pregnancy and postpartum ( 33 , 43 ). Together, these findings indicate that Cr+PCr is a viable reference molecule for MRS research in PM women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some amino acids and their precursors act as the neurotransmitters in the regulation of depressive symptoms. For example, glutamate, an important excitatory neurotransmitter, is usually observed at low levels in the prefrontal cortex of women with late pregnancy or postpartum depression ( 19 ). It can be restored in the dorsolateral prefrontal cortex after progesterone treatment ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The perinatal period alone is associated with substantial changes in the brain connectivity and structural integrity in healthy mothers, as their brains undergo the process of adaptation to the maternal caregiving ( 12 , 13 ). Considering these essential transformations, it is of interest to examine whether the PPD brain features differ from those observed in a non-depressed peripartum mother.…”
Section: Introductionmentioning
confidence: 99%